Absolute structure of resveratrol hexamers in Dipterocarpaceaeous plants. Issue 7 (18th February 2016) - Ito, Tetsuro; Hara, Yasumasa; Kubota, Yumiko; Sawa, Ryuichi; Iinuma, Munekazu
Abstract: A resveratrol (Res) hexamer (vaticanol M (1 )) and two O -glucosides of1 (vatcasides E (2 ) and F (3 )) and an epimer of2 (vatcaside G (4 )) were isolated from three Vatica species— Vatica bantamensis, Vatica chinensis, and Vatica albiramis . The structures with a 3-(3, 5-dihydroxyphenyl)-4, 6-dihydroxy-2-(4-hydroxyphenyl)-2, 3-dihydro-1 H -inden-1-yl group on the C-12 position of (−)-vaticanol B (5 ) were elucidated by spectroscopic analysis, including NMR experiments, conformational search by a MacroModel module, and circular dichroism data. Graphical abstract: